The diagnostic accuracy of PTSD assessment instruments used in older adults: a systematic review - Demi C. D. Havermans; Estelle M. N. Coeur; Jiaqing O; Colton S. Rippey; Joan M. Cook; Miranda Olff; Chris Hoeboer; Sjacko Sobczak; Karen A. Lawrence (European Journal of Psychotraumatology)
Background: As the number of older adults increases worldwide, understanding their mental health is crucial, including the impact of traumatic experiences that can lead to posttraumatic stress disorder (PTSD). However, validated screening and diagnostic instruments for PTSD in older adults are limited.Objective: We sought to provide a comprehensive summary of the diagnostic accuracy of PTSD screening and diagnostic instruments used in older adults (Mage ≥ 60 years).Method: A systematic search of MEDLINE, EMBASE, PsycINFO and Web of Science databases was conducted for January 1980 through 10 January 2025. Studies that focused on the psychometric properties of PTSD instruments in older adults were included.Results: Out of 21,197 publications screened, only 40 studies including 24 instruments met the eligibility criteria. Only seven were conducted with participants from the general population or primary care patient samples. There were 14 relevant studies in the last ten years, with only six based on the Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition (DSM-5) criteria. Validation studies conducted in non-Western and/or non-English speaking older adult samples are rare.Conclusions: There is a shortage of validation studies of PTSD screening and diagnostic tools in the general older adult population. We recommend using the Clinician-Administered PTSD Scale for DSM-5 in clinical practice. It is the gold standard for assessing current and lifetime PTSD in the general population. Further research is required to establish evidence-based clinical cut-off scores and cross-cultural validity for PTSD screening in different populations of older adults. Future studies should also assess measures that consider the multimorbidity in this population (e.g. cognitive impairment and other psychiatric or medical disorders) and are easy to administer in clinical practice.